Determination of single-crystal elasticity constants of the beta phase in a multiphase tungsten thin film using impulse excitation technique, X-ray diffraction and micro-mechanical modeling. (15th August 2019) - Slim, Mohamed Fares; Alhussein, Akram; Zgheib, Elia; François, Manuel
Abstract: The scope of this work is to propose a methodology allowing the determination of the single-crystal elasticity constants of a phase included in a multiphase thin film taking into account its microstructure (crystallographic and morphological texture, porosity and multiphase aspect). The methodology is based on the use of a macro-mechanical test, the impulse excitation technique, a micro-mechanical test, X-ray diffraction and the Kröner-Eshelby scale transition model. As a supporting example, it was applied to determine the single-crystal elasticity constants of the Wβ tungsten metastable phase embedded in a two phases (α+β) tungsten thin film deposited on a steel substrate by DC magnetron sputtering. The effects of the grain-shape, the crystallographic texture, the porosity and the Wβ volume fraction on the macroscopic elasticity constants were studied. Among all these effects, it was found that the effect of the Wβ volume fraction was the most pronounced. The effects of the crystallographic and morphological texture on the microscopic elastic behavior of the film were evaluated. No dominance of the crystallographic or morphological texture effect was observed and their contributions depend on the crystallographic plane and the measurement direction. Graphical abstract: Schematic representation of the methodology used in the determination of the single-crystal elasticity constants. Image 1